Quasi-Fully Cancellation Fuzzy Modules - Khalaf, Hatem Yahya; Rashed, Hadi Ghali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper it was presented the idea quasi-fully cancellation fuzzy modules and we will denote it by  Q-FCF(M), condition universalistic idea quasi-fully cancellation modules It .has been circulated to this idea quasi-max fully cancellation fuzzy modules and we will denote it by Q-MFCF(M). Lot of results and properties have been studied in this research.